NILAI-NILAI KEISLAMAN DALAM TRADISI TAHLILAN PADA MASYARAKAT SUNGAI MALAYA KABUPATEN KUBU RAYA - Sopyan, Ahmad; Hudin, Hafid; Nugraha, Muhamad Tisna (As-Syifa: Journal of Islamic Studies and History, 2025)
The Tahlilan tradition is a significan cultural practice in indonesia that continues to be preserved. This is related not only to theological beliefs, but also to the socio-cultural traditions that accompany it. This study is important for several reasons. Firstly, as an effort to document and preserve the cultural heritage that reflects the characteristics of Islam Nusantara. Secondly, to understand how local communities adapt and Islamic teachings into the practice of daily life. Thirdly, as a learning model on how the universal values of Islam can be harmonised with local traditions without losing the essence of both. This research aims to identify and analyse the process of tahlilan implementation and the form of Islamic values in the tradition. This research uses a qualitative research method with a descriptive approach. Data collection techniques were observation and interview. The data analysis technique is to read and study the Tahlilan tradition, then interpret the data and adjust it to the theory, the last step is to conclude all of the research results. Data validity techniques with four stages: credibility, transferability , dependability , and confirmability.